Error analysis of long essays and thesis acknowledgements by Nigerian students (2017)
Grammatical errors which manifest as a result of poor mastery of the English language by Nigerians have been extensively discussed by scholars. Errors in different types of writings, including projects, long essays, dissertations and theses have equally been well discussed by scholars. However, to the best of our knowledge, these kinds of studies have not been extended to the analysis of errors in the acknowledgments of such works. This is exactly what this work addressed. This paper examined the acknowledgments of long essays of twenty students with the aim of identifying the errors that are commonly found among undergraduates and postgraduate students. Thirty-five faulty sentences were extracted from twenty projects for analysis. The basic concept of Error Analysis, which is an integral element of the Systemic Grammar, formed the theoretical basis of the work. Acknowledgments pages of students are usually replete with different grammatical errors. These errors could be classified into five categories. The first few pages of the long essays which are usually trivialized by supervisees and supervisors are very important. This is because they can mar the quality of a work. Thus, we recommend that students should write them carefully and consciously, while their supervisors should take time to meticulously go through them in order to correct these errors. This will ultimately improve the quality of the use of English among undergraduates and postgraduate students